2001
DOI: 10.1143/jjap.40.2814
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TaOxNy Gate Dielectric with Improved Thermal Stability

Abstract: The gamma-ray blazar 1611+343 was observed with polarization VLBI mode at 5 GHz in February 1999. The total intensity (I) VLBI image of the source shows a core-jet structure. The jet bends eastward at ∼ 3 mas south of the core. Four components have been detected from results of fitting, with apparent speeds estimated at 6.7 ± 0.7, 2.5 ± 0.3, 4.5 ± 0.5 h −1 c for three jet components (taking H 0 = 100 h km s −1 Mpc −1 , q 0 = 0.5). The polarization (P ) VLBI image of 1611+343 displays the polarized configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…[3][4][5][6][7][8] However, too much nitrogen in the film results in higher positive interface charges, which leads to higher hysteresis and reduced channel mobility. 9 For a gate dielectric, not only the band gap ͑E g ͒ but also the valence band offset as well as the conduction band offset to Si substrate are the most important factors, especially in determining the level of the gate leakage current and assessing high-k gate dielectric in future CMOS device technology. 10,11 Ikarashi et al have reported that nitrogen incorporation reduced the band gap of HfSiO films by 1 eV.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] However, too much nitrogen in the film results in higher positive interface charges, which leads to higher hysteresis and reduced channel mobility. 9 For a gate dielectric, not only the band gap ͑E g ͒ but also the valence band offset as well as the conduction band offset to Si substrate are the most important factors, especially in determining the level of the gate leakage current and assessing high-k gate dielectric in future CMOS device technology. 10,11 Ikarashi et al have reported that nitrogen incorporation reduced the band gap of HfSiO films by 1 eV.…”
mentioning
confidence: 99%
“…The changes in the nitrogen content at the HfO x N y /Si interface ensured differenced in the electrical behavior of devices fabricated employing optimal and non-optimal processes, as discussed above. It has been demonstrated in the literature that different nitrogen content could influence the performance of MOS devices—not only in the case of hafnia-based dielectric materials [ 38 ], but also in the case of SiO x N y /Si structures [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…5) For example, time to breakdown (t BD ) of 4 nm ZrO 2 has been increased from 8 to 1000 s by 3.3 V voltage stress. 6) Although in situ incorporation of nitrogen in high-k gate oxides have been reported for CVD, 7) it has rarely been studied for ALD. Only a brief report on nitrogen addition to oxygen plasma for PE-ALD of ZrO 2 and Al 2 O 3 is found, without detailed study on electrical properties and microstructures.…”
Section: Introductionmentioning
confidence: 99%